High-light-transmittance contact lens silicon hydrogel material and preparation method thereof

By combining silane monomers, functional monomers, crosslinking agents and initiators in specific proportions, the transmittance and antibacterial problems of silicone hydrogel contact lens materials were solved, and a contact lens material with high transmittance and good antibacterial properties was prepared.

CN120737256APending Publication Date: 2025-10-03IRIS (XIAMEN) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510941370.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

The existing silicone hydrogel contact lens materials have a decreased light transmittance due to the incompatibility between the silane monomer and the hydrophilic monomer during the polymerization reaction, and the material has insufficient antibacterial properties and cannot meet the requirements of use.

Method used

By combining silane monomers, functional monomers, crosslinking agents and initiators in specific proportions, functional monomers are introduced during the preparation process to increase the hydrophilicity and antibacterial properties of the material, and high-transmittance contact lens silicone hydrogel materials are prepared using photocuring and dry demolding technology.

Benefits of technology

The silicone hydrogel material has high light transmittance, strong antibacterial properties and appropriate water content, meeting the requirements of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-light-transmittance contact lens silicone hydrogel material and a preparation method thereof, and relates to the technical field of contact lens materials, the high-light-transmittance contact lens silicone hydrogel material comprises the following raw materials by weight: 25-35 parts of a silane monomer, 20-25 parts of a functional monomer, 0.6-1.0 part of a cross-linking agent, 0.3-0.5 part of an initiator, and 40-50 parts of a solvent. The silane monomer, the functional monomer and the cross-linking agent are combined for use, so that the high light transmittance of the prepared silicon hydrogel material meets the use requirement. The functional monomer is prepared from 4-nitrophenyl-beta-D-glucuronic acid sodium salt, 2-cyano-5-(dimethylamino)-3-ethoxy penta-2, 4-dienoic acid ethyl ester, 5-chloro-2-pentanone and the like through a reaction, and the contact lens silicon hydrogel material is endowed with relatively high water content and relatively strong antibacterial property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of contact lens materials, and in particular to a high-transmittance contact lens silicone hydrogel material and a preparation method thereof. Background Art

[0002] Silicone hydrogel material is a contact lens material with excellent oxygen permeability. It can be obtained by mixing silane monomers, hydrophilic monomers, crosslinking agents and initiators and then conducting free radical polymerization or copolymerization reaction, and has a cross-linked hydrogel network structure. Silane monomers are the key to ensuring the high oxygen permeability of silicone hydrogel contact lens materials, but the silane monomers are highly hydrophobic, which will cause the water content of the material to decrease, and then cause the lens surface to shrink or crack, which will have an adverse effect on the transmittance of the contact lens material. Therefore, it is necessary to add hydrophilic monomers, but the incompatibility between hydrophilic monomers and hydrophobic monomers will lead to excessive crosslinking in the polymerization reaction, which will cause the transmittance of the material to decrease. In addition, during the use of contact lenses, microorganisms such as bacteria and viruses will inevitably be adsorbed, causing severe inflammatory reactions, so higher requirements are placed on the antibacterial properties of silicone hydrogel materials.

[0003] In summary, there is an urgent need for a suitable modification method to control the reasonable dosage of silane monomer, hydrophilic monomer, crosslinker and initiator, so that the transmittance of silicone hydrogel contact lens material meets the use requirements and the silicone hydrogel contact lens material is given good antibacterial properties and appropriate water content. Summary of the Invention

[0004] In order to solve the above technical problems, the present invention provides a high-transmittance contact lens silicone hydrogel material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-transmittance contact lens silicone hydrogel material comprises the following raw materials in parts by weight: 25-35 parts of a silane monomer, 20-25 parts of a functional monomer, 0.6-1.0 parts of a cross-linking agent, 0.3-0.5 parts of an initiator, and 40-50 parts of a solvent; Furthermore, the crosslinking agent is 1,6-hexanediol di(meth)acrylate; the initiator is a mixture of photoinitiator 184 and photoinitiator 1173 in a mass ratio of 1-1.5:1.5-2; the solvent is a mixture of n-butanol and n-hexanol in a volume ratio of 1:1-1.5; The preparation of the high-transmittance contact lens silicone hydrogel material comprises the following steps: Step R1, cyclosiloxane, tetramethyldisiloxane, DMSO, and toluene are mixed, trifluoromethanesulfonic acid is added, the mixture is heated and stirred, potassium bicarbonate is added and stirred, and the mixture is rotary evaporated and vacuum dried to obtain a silane monomer; Step R2, mixing a silane monomer, a functional monomer, a crosslinking agent, an initiator, and a solvent to obtain a dispersion system, and dropwise adding the dispersion system to a contact lens mold that has been pre-filled with nitrogen and preheated, followed by light curing, and then dry demolding to obtain a high-transmittance contact lens silicone hydrogel material; The preparation of the high-transmittance contact lens silicone hydrogel material comprises the following specific steps: Step R1, cyclosiloxane, tetramethyldisiloxane, DMSO, and toluene were mixed and stirred for 30-40 minutes, trifluoromethanesulfonic acid was added, the temperature was raised to 55-60° C., and the mixture was stirred for 5-6 hours. Potassium bicarbonate was added and stirred for 15-20 minutes, and the mixture was rotary evaporated and vacuum dried to obtain a silane monomer; Furthermore, the usage ratio of cyclosiloxane, tetramethyldisiloxane, DMSO, toluene, trifluoromethanesulfonic acid, and potassium bicarbonate is 11-13 g: 0.1-0.3 g: 35-55 mL: 15-30 mL: 0.02-0.03 g: 6-10 mg; the cyclosiloxane is octamethylcyclotetrasiloxane; the tetramethyldisiloxane is diallyltetramethyldisiloxane; During the reaction of step R1, cyclosiloxane is subjected to ring-opening polymerization under the action of tetramethyldisiloxane and trifluoromethanesulfonic acid to obtain a silane monomer containing a terminal carbon-carbon double bond; Step R2, mixing the silane monomer, functional monomer, crosslinking agent, initiator, and solvent and stirring for 45-50 minutes to obtain a dispersion system, adding the dispersion system dropwise to a contact lens mold that has been pre-filled with nitrogen and preheated at 45-50° C., then performing light curing, and then dry demolding to obtain a high-transmittance contact lens silicone hydrogel material; Furthermore, the conditions for light curing are: using a 365nm LED lamp as the light source, at 1mW / cm 2 Curing under the light intensity of 8-10min, and then at 3mW / cm 2 The dry demoulding method is as follows: place the contact lens mold in an oven at 25-30°C for 8-10 minutes, then gently press the edge of the mold with a silicone gasket, and then pull out the lens vertically; The preparation of the functional monomer comprises the following steps: Step H1: Mix the nitro compound and solvent 1, add ammonia water and hydrosulfite, and stir at room temperature to obtain product a; under a protective gas atmosphere, mix ethyl dienoate and DMAC, increase the temperature, add product a and ammonium chloride, and stir to obtain product b; Step H2: Under a protective gas atmosphere, 5-chloro-2-pentanone was added to anhydrous tetrahydrofuran, and the mixture was stirred. Methylenetriphenylphosphine was then added, and the mixture was heated and refluxed with stirring to obtain product c. Product b, product c, and ethanol were mixed, and the mixture was heated and stirred to obtain product d. Step H3: Mix product d, toluene, and tetrahydrofuran, add diisopropylamine borane and lithium borohydride in a protective gas atmosphere, and heat and stir to obtain a functional monomer; The preparation of the functional monomer comprises the following specific steps: Step H1: Mix the nitro compound and solvent 1 and stir for 30-40 minutes, then add ammonia water and hydrosulfite, and stir and react at room temperature for 1-1.5 hours to obtain product a. Under a protective gas atmosphere, mix ethyl dienoate and DMAC, raise the temperature to 85-95°C, add product a and ammonium chloride, and stir and react for 7-7.5 hours to obtain product b. Furthermore, the dosage ratio of the nitro compound, solvent 1, ammonia water, and sodium hydrosulfite is 35-37 g:125-135 mL:0.3-0.5 mL:25-27 g; the nitro compound is 4-nitrophenyl-β-D-glucuronic acid sodium salt; the solvent 1 is obtained by mixing 1,4-dioxane and water in a volume ratio of 2:1-1.5; the mass fraction of ammonia water is 28%; the ethyl dienoate is ethyl 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoate; and the dosage ratio of the ethyl dienoate, DMAC, product a, and ammonium chloride is 25-27 g:130-140 mL:33-35 g:0.6-0.8 g. During the reaction of step H1, the nitro group of the nitro compound is reduced to an amino group, retaining the conjugated diene to obtain product a; the ester group of the dienoic acid ethyl ester reacts with the amino group of product a to obtain product b; Step H2: Under a protective gas atmosphere, add 5-chloro-2-pentanone to anhydrous tetrahydrofuran, stir for 10-15 minutes, add methylenetriphenylphosphine, heat to 45-55°C, and reflux with stirring for 11-11.5 hours to obtain product c; mix product b, product c, and ethanol, heat to 50-60°C, and stir for 5.5-6.5 hours to obtain product d; Furthermore, the usage ratio of 5-chloro-2-pentanone, anhydrous tetrahydrofuran, and methylenetriphenylphosphine is 15-17 g: 95-105 mL: 30-32 g; the usage ratio of product b, product c, and ethanol is 60-62 g: 13-15 g: 155-165 mL; and the volume fraction of ethanol is 95%; During the reaction of step H2, the ketone carbon of 5-chloro-2-pentanone reacts with methylenetriphenylphosphine to obtain product c containing a terminal carbon-carbon double bond; the tertiary amine of product b reacts with the alkyl chloride of product c to obtain product d containing a quaternary ammonium salt; Step H3: Product d, toluene, and tetrahydrofuran were mixed and stirred for 15-20 minutes, diisopropylamine borane and lithium borohydride were added under a protective gas atmosphere, the temperature was raised to 40-50° C., and the mixture was stirred and reacted for 6-6.5 hours to obtain a functional monomer; Furthermore, the usage ratio of product d, toluene, tetrahydrofuran, diisopropylamine borane, and lithium borohydride is 70-75 g: 100-110 mL: 60-70 mL: 15-17 g: 0.4-0.6 g; During the reaction of step H3, the cyano group of product d is selectively reduced to an amino group, retaining the conjugated diene, to obtain a functional monomer containing sodium glucuronic acid, a primary amino group, a conjugated diene, a quaternary ammonium salt, and a terminal carbon-carbon double bond; Beneficial effects of the present invention: The present invention discloses a high-transmittance contact lens silicone hydrogel material and a preparation method thereof. The high-transmittance contact lens silicone hydrogel material is prepared from raw materials such as silane monomer, functional monomer, cross-linking agent, initiator, and solvent. By combining the silane monomer, functional monomer, and cross-linking agent, the high transmittance of the prepared silicone hydrogel material meets the use requirements.

[0006] The functional monomer is obtained by reacting 4-nitrophenyl-β-D-glucuronic acid sodium salt, 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoic acid ethyl ester, 5-chloro-2-pentanone, etc., and contains groups such as sodium glucuronic acid, primary amino group, conjugated diene, quaternary ammonium salt, and terminal carbon-carbon double bond. The combined use of 4-nitrophenyl-β-D-glucuronic acid sodium salt, 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoic acid ethyl ester, and 5-chloro-2-pentanone allows sodium glucuronic acid, primary amino groups, and quaternary ammonium salts to produce a synergistic hydrophilic effect within the molecule, which is beneficial for increasing the water content of the silicone hydrogel material. The introduction of primary amino groups into the molecules containing the quaternary ammonium salt enhances the antibacterial properties of the quaternary ammonium salt. After the functional monomer participates in the polymerization reaction, the stability of the quaternary ammonium salt in the material is enhanced. The quaternary ammonium salt and the conjugated diene have a synergistic antibacterial effect within the molecule, giving the silicone hydrogel material strong antibacterial properties. DETAILED DESCRIPTION

[0007] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0008] Example 1 A functional monomer, the preparation of which comprises the following steps: Step H1: 4-nitrophenyl-β-D-glucuronic acid sodium salt and solvent 1 were mixed and stirred for 30 minutes, ammonia water and hydrosulfite were added, and the mixture was stirred and reacted at room temperature for 1 hour to obtain product a; in a nitrogen atmosphere, 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoic acid ethyl ester and DMAC were mixed, the temperature was raised to 85° C., product a and ammonium chloride were added, and the mixture was stirred and reacted for 7 hours to obtain product b; 4-nitrophenyl-β-D- The dosage ratio of glucuronic acid sodium salt, solvent 1, ammonia water, and hydrosulfite is 35 g:125 mL:0.3 mL:25 g; solvent 1 is a mixture of 1,4-dioxane and water in a volume ratio of 2:1; the mass fraction of ammonia water is 28%; the dosage ratio of 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoic acid ethyl ester, DMAC, product a, and ammonium chloride is 25 g:130 mL:33 g:0.6 g; Step H2: Under a nitrogen atmosphere, 5-chloro-2-pentanone was added to anhydrous tetrahydrofuran, stirred for 10 min, and methylenetriphenylphosphine was added. The temperature was raised to 45°C, and the mixture was refluxed with stirring for 11 h to obtain product c. Product b, product c, and ethanol were mixed, the temperature was raised to 50°C, and the mixture was stirred for 5.5 h to obtain product d. The amount ratio of 5-chloro-2-pentanone, anhydrous tetrahydrofuran, and methylenetriphenylphosphine was 15 g:95 mL:30 g; the amount ratio of product b, product c, and ethanol was 60 g:13 g:155 mL; the volume fraction of ethanol was 95%. Step H3: Product d, toluene, and tetrahydrofuran were mixed and stirred for 15 minutes. Diisopropylamine borane and lithium borohydride were added in a nitrogen atmosphere. The temperature was raised to 40°C, and the mixture was stirred for 6 hours to obtain a functional monomer. The dosage ratio of product d, toluene, tetrahydrofuran, diisopropylamine borane, and lithium borohydride was 70 g:100 mL:60 mL:15 g:0.4 g.

[0009] Example 2 A functional monomer, the preparation of which comprises the following steps: Step H1: 4-nitrophenyl-β-D-glucuronic acid sodium salt and solvent 1 were mixed and stirred for 35 minutes, ammonia water and hydrosulfite were added, and the mixture was stirred and reacted at room temperature for 1-1.5 hours to obtain product a; in a nitrogen atmosphere, 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoic acid ethyl ester and DMAC were mixed, the temperature was raised to 90°C, product a and ammonium chloride were added, and the mixture was stirred and reacted for 7.3 hours to obtain product b; 4-nitrophenyl-β- The ratio of D-glucuronic acid sodium salt, solvent 1, ammonia water, and hydrosulfite is 36 g:130 mL:0.4 mL:26 g; solvent 1 is a mixture of 1,4-dioxane and water in a volume ratio of 2:1.3; the mass fraction of ammonia water is 28%; the ratio of 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoic acid ethyl ester, DMAC, product a, and ammonium chloride is 26 g:135 mL:34 g:0.7 g; Step H2: Under a nitrogen atmosphere, 5-chloro-2-pentanone was added to anhydrous tetrahydrofuran, stirred for 13 minutes, and methylenetriphenylphosphine was added. The temperature was raised to 50°C, and the mixture was refluxed with stirring for 11.3 hours to obtain product c. Product b, product c, and ethanol were mixed, the temperature was raised to 55°C, and the mixture was stirred for 6.0 hours to obtain product d. The amount ratio of 5-chloro-2-pentanone, anhydrous tetrahydrofuran, and methylenetriphenylphosphine was 16 g:100 mL:31 g; the amount ratio of product b, product c, and ethanol was 61 g:14 g:160 mL; the volume fraction of ethanol was 95%. Step H3: Product d, toluene, and tetrahydrofuran were mixed and stirred for 18 minutes. Diisopropylamine borane and lithium borohydride were added in a nitrogen atmosphere. The temperature was raised to 45°C, and the mixture was stirred for 6.3 hours to obtain a functional monomer. The usage ratio of product d, toluene, tetrahydrofuran, diisopropylamine borane, and lithium borohydride was 73 g:105 mL:65 mL:16 g:0.5 g.

[0010] Example 3 A functional monomer, the preparation of which comprises the following steps: Step H1: 4-nitrophenyl-β-D-glucuronic acid sodium salt and solvent 1 were mixed and stirred for 40 minutes, ammonia water and hydrosulfite were added, and the mixture was stirred and reacted at room temperature for 1.5 hours to obtain product a; in a nitrogen atmosphere, 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoic acid ethyl ester and DMAC were mixed, the temperature was raised to 95° C., product a and ammonium chloride were added, and the mixture was stirred and reacted for 7.5 hours to obtain product b; 4-nitrophenyl-β-D The ratio of sodium glucuronic acid salt, solvent 1, ammonia water, and hydrosulfite is 37 g:135 mL:0.5 mL:27 g; solvent 1 is a mixture of 1,4-dioxane and water in a volume ratio of 2:1.5; the mass fraction of ammonia water is 28%; the ratio of ethyl 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoate, DMAC, product a, and ammonium chloride is 27 g:140 mL:35 g:0.8 g; Step H2: Under a nitrogen atmosphere, 5-chloro-2-pentanone was added to anhydrous tetrahydrofuran, stirred for 15 minutes, and methylenetriphenylphosphine was added. The temperature was raised to 55°C, and the mixture was refluxed with stirring for 11.5 hours to obtain product c. Product b, product c, and ethanol were mixed, the temperature was raised to 60°C, and the mixture was stirred for 6.5 hours to obtain product d. The amount ratio of 5-chloro-2-pentanone, anhydrous tetrahydrofuran, and methylenetriphenylphosphine was 17 g:105 mL:32 g; the amount ratio of product b, product c, and ethanol was 62 g:15 g:165 mL; the volume fraction of ethanol was 95%. Step H3: Product d, toluene, and tetrahydrofuran were mixed and stirred for 20 minutes. Diisopropylamine borane and lithium borohydride were added in a nitrogen atmosphere. The temperature was raised to 50°C, and the reaction was stirred for 6.5 hours to obtain a functional monomer. The usage ratio of product d, toluene, tetrahydrofuran, diisopropylamine borane, and lithium borohydride was 75 g:110 mL:70 mL:17 g:0.6 g.

[0011] Example 4 A high-transmittance contact lens silicone hydrogel material comprises the following raw materials in parts by weight: 25 parts of a silane monomer, 20 parts of a functional monomer, 0.6 parts of a crosslinker, 0.3 parts of an initiator, and 40 parts of a solvent; the crosslinker is 1,6-hexanediol di(meth)acrylate; the initiator is a mixture of photoinitiator 184 and photoinitiator 1173 in a mass ratio of 1:1.5; and the solvent is a mixture of n-butanol and n-hexanol in a volume ratio of 1:1. The preparation of the high-transmittance contact lens silicone hydrogel material comprises the following steps: Step R1, octamethylcyclotetrasiloxane, diallyltetramethyldisiloxane, DMSO, and toluene were mixed and stirred for 30 minutes, trifluoromethanesulfonic acid was added, the temperature was raised to 55°C, and the mixture was stirred for 5 hours. Potassium bicarbonate was added and stirred for 15 minutes. The mixture was rotary evaporated and vacuum dried to obtain a silane monomer; the dosage ratio of octamethylcyclotetrasiloxane, diallyltetramethyldisiloxane, DMSO, toluene, trifluoromethanesulfonic acid, and potassium bicarbonate was 11 g: 0.1 g: 25 mL: 15 mL: 0.02 g: 6 mg; Step R2: Silane monomer, the functional monomer obtained in Example 1, a crosslinking agent, an initiator, and a solvent were mixed and stirred for 45 minutes to obtain a dispersion system, and the dispersion system was added dropwise to a contact lens mold that had been pre-filled with nitrogen and preheated at 45°C, and then photocured. After that, the mold was demolded by dry method to obtain a high-transmittance contact lens silicone hydrogel material; the photocuring conditions were: a 365nm LED lamp was used as the light source, and the wavelength was 1mW / cm 2 Curing at 8min under the light intensity of 3mW / cm 2 The dry demoulding method is as follows: place the contact lens mold in an oven at 25°C for 8 minutes, then gently press the edge of the mold with a silicone gasket and then pull out the lens vertically.

[0012] Example 5 A high-transmittance contact lens silicone hydrogel material comprises the following raw materials in parts by weight: 30 parts of a silane monomer, 23 parts of a functional monomer, 0.8 parts of a crosslinker, 0.4 parts of an initiator, and 45 parts of a solvent; the crosslinker is 1,6-hexanediol di(meth)acrylate; the initiator is a mixture of photoinitiator 184 and photoinitiator 1173 in a mass ratio of 1.3:1.8; and the solvent is a mixture of n-butanol and n-hexanol in a volume ratio of 1:1.3. The preparation of the high-transmittance contact lens silicone hydrogel material comprises the following steps: Step R1, octamethylcyclotetrasiloxane, diallyltetramethyldisiloxane, DMSO, and toluene were mixed and stirred for 35 minutes, trifluoromethanesulfonic acid was added, the temperature was raised to 58°C, and the reaction was stirred for 5.5 hours. Potassium bicarbonate was added and stirred for 18 minutes. The mixture was rotary evaporated and vacuum dried to obtain a silane monomer; the dosage ratio of octamethylcyclotetrasiloxane, diallyltetramethyldisiloxane, DMSO, toluene, trifluoromethanesulfonic acid, and potassium bicarbonate was 12g:0.2g:45mL:22mL:0.025g:8mg; Step R2: Silane monomer, the functional monomer obtained in Example 2, a crosslinking agent, an initiator, and a solvent were mixed and stirred for 48 minutes to obtain a dispersion system, and the dispersion system was added dropwise to a contact lens mold that had been pre-filled with nitrogen and preheated at 48°C, and then photocured, followed by dry demolding to obtain a high-transmittance contact lens silicone hydrogel material; the photocuring conditions were: a 365nm LED lamp was used as the light source, at 1mW / cm 2 Curing under the light intensity of 9min, and then at 3mW / cm 2 The dry demoulding method is as follows: place the contact lens mold in an oven at 27°C for 9 minutes, then gently press the edge of the mold with a silicone gasket and then pull out the lens vertically.

[0013] Example 6 A high-transmittance contact lens silicone hydrogel material comprises the following raw materials in parts by weight: 35 parts of a silane monomer, 25 parts of a functional monomer, 1.0 part of a crosslinker, 0.5 parts of an initiator, and 50 parts of a solvent; the crosslinker is 1,6-hexanediol di(meth)acrylate; the initiator is a mixture of photoinitiator 184 and photoinitiator 1173 in a mass ratio of 1.5:2; and the solvent is a mixture of n-butanol and n-hexanol in a volume ratio of 1:1.5. The preparation of the high-transmittance contact lens silicone hydrogel material comprises the following steps: Step R1, octamethylcyclotetrasiloxane, diallyltetramethyldisiloxane, DMSO, and toluene were mixed and stirred for 40 minutes, trifluoromethanesulfonic acid was added, the temperature was raised to 60°C, and the reaction was stirred for 6 hours. Potassium bicarbonate was added and stirred for 20 minutes. The mixture was rotary evaporated and vacuum dried to obtain a silane monomer; the amount ratio of octamethylcyclotetrasiloxane, diallyltetramethyldisiloxane, DMSO, toluene, trifluoromethanesulfonic acid, and potassium bicarbonate was 13g:0.3g:55mL:30mL:0.03g:10mg; Step R2: Silane monomer, the functional monomer obtained in Example 3, a crosslinking agent, an initiator, and a solvent were mixed and stirred for 50 minutes to obtain a dispersion system, and the dispersion system was added dropwise to a contact lens mold that had been pre-filled with nitrogen and preheated at 50°C, and then photocured. After that, the mold was demolded by dry method to obtain a high-transmittance contact lens silicone hydrogel material; the photocuring conditions were: a 365nm LED lamp was used as the light source, and the wavelength was 1mW / cm 2 Curing for 10 min at a light intensity of 3 mW / cm 2 The dry demoulding method is as follows: place the contact lens mold in an oven at 30°C for 10 minutes, gently press the edge of the mold with a silicone gasket, and then pull out the lens vertically.

[0014] Comparative Example 1 Compared with Example 6, the functional monomer was replaced with 2-aminoethyl methacrylate, and the rest was exactly the same as Example 6 to prepare a contact lens silicone hydrogel material.

[0015] Comparative Example 2 Compared with Example 6, the product a in the preparation process of the functional monomer was replaced with chitosan, and the rest was exactly the same as Example 6 to prepare a contact lens silicone hydrogel material.

[0016] Comparative Example 3 Compared with Example 6, the functional monomer was replaced with product d, and the rest was exactly the same as Example 6 to prepare a contact lens silicone hydrogel material.

[0017] The effect of the contact lens silicone hydrogel material prepared by the present invention was further tested below, and the test results are described below.

[0018] Light transmittance: Place the silicone hydrogel close to the optical glass translucent surface of a cuvette filled with physiological saline, use physiological saline as a reference, and measure its light transmittance at an emission wavelength of 400-700nm; Antibacterial property: Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus were used as test bacteria to test the antibacterial rate of the obtained contact lens silicone hydrogel material; Water content: Soak the obtained contact lens silicone hydrogel material in distilled water overnight, remove it and absorb all surface moisture with filter paper, weigh the weight m1, and then dry it at 105°C to constant weight. Measure the constant weight m2. Measure three sets of parallel samples and calculate the water content according to the formula: water content = (m1-m2) / m1×100%. Take the average water content as the water content value; The results are recorded in Table 1; Table 1: Test results

[0019] According to the data in Table 1, silicone hydrogel contact lens material of the present invention has high transmittance, stronger antibacterial property, higher water content. Embodiment 6 is compared with comparative example 1 and can be known that, functional monomer is replaced by 2-aminoethyl methacrylate, and the transmittance, antibacterial property, water content of material decline more. Embodiment 6 is compared with comparative example 2 and can be known that, product a in the functional monomer preparation process is replaced by chitosan, hydrophilicity declines, and antibacterial property is basically unchanged, and the transmittance of material declines to some extent, water content declines. Embodiment 6 is compared with comparative example 3 and can be known that, functional monomer is replaced by product d, hydrophilicity declines, and the antibacterial property of strengthening quaternary ammonium salt declines, causing the transmittance of material to decline, antibacterial property to decline, water content to decline.

[0020] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.

Claims

1. A high-transmittance silicone hydrogel material for contact lenses, characterized by: The method comprises the following raw materials in parts by weight: 25-35 parts of silane monomer, 20-25 parts of functional monomer, 0.6-1.0 parts of crosslinking agent, 0.3-0.5 parts of initiator, and 40-50 parts of solvent; The preparation of the functional monomer comprises the following steps: Step H1: Mix the nitro compound and solvent 1, add ammonia water and hydrosulfite, and stir at room temperature to obtain product a; under a protective gas atmosphere, mix ethyl dienoate and DMAC, increase the temperature, add product a and ammonium chloride, and stir to obtain product b; Step H2: Under a protective gas atmosphere, 5-chloro-2-pentanone was added to anhydrous tetrahydrofuran, and the mixture was stirred. Methylenetriphenylphosphine was then added, and the mixture was heated and refluxed with stirring to obtain product c. Product b, product c, and ethanol were mixed, and the mixture was heated and stirred to obtain product d. Step H3: Mix product d, toluene, and tetrahydrofuran, add diisopropylamine borane and lithium borohydride in a protective gas atmosphere, and heat and stir to obtain a functional monomer.

2. The high-transmittance contact lens silicone hydrogel material according to claim 1, characterized in that: The initiator is obtained by mixing photoinitiator 184 and photoinitiator 1173 in a mass ratio of 1-1.5:1.5-2; the solvent is obtained by mixing n-butanol and n-hexanol in a volume ratio of 1:1-1.

5.

3. The high-transmittance contact lens silicone hydrogel material according to claim 1, characterized in that: The preparation process of the silane monomer is as follows: cyclosiloxane, tetramethyldisiloxane, DMSO and toluene are mixed, trifluoromethanesulfonic acid is added, the mixture is heated and stirred, potassium bicarbonate is added and stirred, and the mixture is rotary evaporated and vacuum dried to obtain the silane monomer.

4. The high-transmittance contact lens silicone hydrogel material according to claim 3, characterized in that: The cyclosiloxane is octamethylcyclotetrasiloxane; and the tetramethyldisiloxane is diallyltetramethyldisiloxane.

5. The high-transmittance contact lens silicone hydrogel material according to claim 1, characterized in that: In step H1, the nitro compound is 4-nitrophenyl-β-D-glucuronic acid sodium salt; and solvent 1 is a mixture of 1,4-dioxane and water in a volume ratio of 2:1-1.

5.

6. The high-transmittance contact lens silicone hydrogel material according to claim 1, characterized in that: In step H1, the ethyl dienoate is ethyl 2-cyano-5-(dimethylamino)-3-ethoxypenta-2,4-dienoate.

7. A method for preparing the high-transmittance contact lens silicone hydrogel material according to any one of claims 1 to 6, characterized in that: The steps include: Silane monomer, functional monomer, crosslinking agent, initiator and solvent are mixed to obtain a dispersion system, which is then added dropwise to a contact lens mold that has been pre-filled with nitrogen and preheated, followed by light curing and dry demoulding to obtain a high-transmittance contact lens silicone hydrogel material.

8. The method for preparing a high-transmittance contact lens silicone hydrogel material according to claim 7, characterized in that: The contact lens mold preheating temperature is 45-50℃; the light curing conditions are: 365nm LED light as the light source, at 1mW / cm 2 Curing under the light intensity of 8-10min, and then at 3mW / cm 2 Curing under light intensity of 18-20min.

9. The method for preparing a high-transmittance contact lens silicone hydrogel material according to claim 7, wherein: The dry demoulding method is as follows: place the contact lens mold in an oven at 25-30℃ for 8-10 minutes, then gently press the edge of the mold with a silicone gasket, and then pull out the lens vertically.